ANALISIS STRATEGI PENJUALAN PUPUK PHONSKA CAIR DI GRESIK - Vita Veronica; Moh Agung Surianto (Universitas Sarjanawiyata Tamansiswa, 2026)
The increasing competition in the fertilizer industry requires companies to implement effective sales strategies to improve market acceptance of innovative products, including Phonska Liquid Fertilizer. This study aims to analyze the sales strategy of Phonska Liquid Fertilizer at PT XYZ, identify the factors influencing farmers' purchasing decisions, and examine the challenges and opportunities for sales development in Gresik Regency. A qualitative descriptive approach was employed. Data were collected through in-depth interviews, observations, and documentation involving the Assistant Vice President of Non-Centralized Retail Operations, sales agents, fertilizer kiosk owners, and farmers selected using purposive sampling. Data were analyzed using the interactive model of Miles and Huberman. The findings indicate that direct selling, demonstration plots (demplot), One Day Promotion (ODP), farmer group socialization, and continuous assistance from sales agents have improved farmers' understanding of and trust in the product. Purchasing decisions are influenced by product quality, price, user experience, brand reputation, and recommendations from fellow farmers. The study implies that successful sales strategies depend not only on product quality but also on the implementation of relationship marketing through continuous education, communication, and technical assistance to enhance product adoption and competitiveness.